2002
DOI: 10.1038/nm801
|View full text |Cite
|
Sign up to set email alerts
|

The neuropeptides GnRH-II and GnRH-I are produced by human T cells and trigger laminin receptor gene expression, adhesion, chemotaxis and homing to specific organs

Abstract: Can T cells be directly activated to de novo gene expression by gonadotropin-releasing hormone-II (GnRH-II), a unique 10-amino-acid neuropeptide conserved through 500 million years of evolution? GnRH-II, which has been identified in mammals, shares 70% homology with the mammalian hypothalamic neurohormone GnRH (GnRH-I), the primary regulator of reproduction, but is encoded by a different gene. Although both neuropeptides are produced mainly in brain, their localization and promoter regulation differ, suggestiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
86
0
3

Year Published

2003
2003
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(89 citation statements)
references
References 0 publications
0
86
0
3
Order By: Relevance
“…For more than a century it has been recognized that androgen deprivation affects the immune system,34 and the GnRH receptor has been found on immune cells from humans35, 36 and rodents 13, 37. Interestingly, stimulation of the GnRH receptor exacerbated lupus in castrated female mice14, 38 and treatment with GnRH receptor antagonist delayed the onset of autoimmune diabetes15 and increased the survival rate among lupus‐prone mice 14.…”
Section: Discussionmentioning
confidence: 99%
“…For more than a century it has been recognized that androgen deprivation affects the immune system,34 and the GnRH receptor has been found on immune cells from humans35, 36 and rodents 13, 37. Interestingly, stimulation of the GnRH receptor exacerbated lupus in castrated female mice14, 38 and treatment with GnRH receptor antagonist delayed the onset of autoimmune diabetes15 and increased the survival rate among lupus‐prone mice 14.…”
Section: Discussionmentioning
confidence: 99%
“…The manner in which local GnRH action modulates the physiology and patho-physiology of reproductive tissues is a focus of investigation [23,48,139]. More specialized roles in blastocyst implantation, physiological changes occurring during pregnancy, including modulation of the cellular immune system, and influences on reproductive and parental behavior are also regarded as possibilities in certain mammalian species [15,19,22,40,59,61]. Many mechanistic questions concerning the precise involvement of GnRH in such diverse processes remain unanswered.…”
Section: Potential Functions Of Gnrh In Mammalsmentioning
confidence: 99%
“…Moreover, in addition to the direct effects on gonads, it has been reported that GnRH may act as a neuromodulator or an immunomodulator. (Eisthen et al ., 2000;Oka, 2002;Ford et al ., 2003;Azad et al ., 1997;Enomoto et al ., 2001;Chen et al ., 2002). Although a number of studies have been performed on these effects of GnRH, little is known about the molecular mechanisms and physiological settings in which GnRH exerts its activities in extrapituitary tissues or organs.…”
Section: Introductionmentioning
confidence: 99%
“…These opposite effects of GnRH on cell proliferation are very interesting, but it has remained unknown whether GnRH has such activities in physiological settings, mainly because most previous studies were performed using cancer cell lines and pharmacological doses of GnRH. However, recently, the effects of GnRH on the cell proliferation of non-tumor cells, as well as on cell adhesion, cell migration, and cytoskeletal remodeling have been reported (Chen et al ., 2002;Romanelli et al ., 2004;Davidson et al ., 2004) and the physiological roles of the effects of GnRH on cell proliferation are being reconsidered.…”
Section: Introductionmentioning
confidence: 99%